Responsabilidade civil decorrente de abandono afetivo paterno/materno filial - Giandoso, Wanessa de Figueiredo (2014)
The scope of this master‟s dissertation is to analyze the possibility of civil liability derived from neglect affective relations between father, mother and children under the focus of the Brazilian Federal Constitution of 1988, the Child and Youth Statute and the Civil-law Code of 2002. Family rights went through several changes. The traditional concept would be related to marriage and to consanguineous ties, remained behind in the 1916 Civil Code. All this transformation took place with Brazil‟s 1988 Federal Constitution, which enshrined broadly the family concept, defining it as an entity and the basis of society, considering it as well as the foundation of psychological, social and emotional development in the individual. After these family paradigm shifts; family affection, mutual respect, conviviality, fellowship and solidarity became the main relations between its members. It is a fundamental right of every human being to be raised alongside with his family. For the parents, it is a duty while having the power upon their family to have their children with them, and raising and educating them in a healthy and friendly environment. Therefore they can provide a complete development of the human personality of the upbringing child. During the exercise of their family power, if the father or the mother acts in a silent and irresponsible way, disrespecting their own legal rights of raising and looking after their children,as well as failing to provide a descent emotional and psychological support to them, will be considered as tort, amenable to repair